2010
DOI: 10.1111/j.1755-5949.2010.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Postconditioning Ameliorates Oxygen–Glucose Deprivation—Reperfusion Injury in the Rat Hippocampus

Abstract: Postconditioning with sevoflurane reduces neuronal damage after OGD-reperfusion injury in the CA1 area of rat hippocampus, in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The neuronal cultures were then directly placed in an anaerobic incubator (Thermo, Waltham, MA, USA) containing 100% N 2 at 37°C. After 90 min in OGD, the cultures were removed from the anaerobic incubator, immediately washed three times with BSS before adding an equal volume of Neuorbasal medium/B27/glutamine/gentamycin and incubated in a standard cell incubator containing 5% CO 2 , 95% air balance, and 98% humidity at 37°C for 24 h. In the sevoflurane postconditioning protocols, neuronal cultures were exposed immediately in a Billups-Rothenburg chamber that was bubbled with 2% of sevoflurane in 95% air-5% CO 2 at 6 L/min for 7-8 min after OGD [20]. Then the chamber was kept tightly sealed for 1 h at 37°C and the concentrations of sevoflurane in exhaust gas from the chamber was confirmed by the Datex™ infrared analyzer (Capnomac, Helsinki, Finland).…”
Section: Ogd/r and Sevoflurane Post-conditioningmentioning
confidence: 99%
“…The neuronal cultures were then directly placed in an anaerobic incubator (Thermo, Waltham, MA, USA) containing 100% N 2 at 37°C. After 90 min in OGD, the cultures were removed from the anaerobic incubator, immediately washed three times with BSS before adding an equal volume of Neuorbasal medium/B27/glutamine/gentamycin and incubated in a standard cell incubator containing 5% CO 2 , 95% air balance, and 98% humidity at 37°C for 24 h. In the sevoflurane postconditioning protocols, neuronal cultures were exposed immediately in a Billups-Rothenburg chamber that was bubbled with 2% of sevoflurane in 95% air-5% CO 2 at 6 L/min for 7-8 min after OGD [20]. Then the chamber was kept tightly sealed for 1 h at 37°C and the concentrations of sevoflurane in exhaust gas from the chamber was confirmed by the Datex™ infrared analyzer (Capnomac, Helsinki, Finland).…”
Section: Ogd/r and Sevoflurane Post-conditioningmentioning
confidence: 99%
“…However, less is known about the postconditioning effect of sevoflurane, a more recent procedure that has also shown to be an effective therapeutic strategy to reduce ischemia-induced damage in the brain and myocardium [30,31] and to attenuate LPS-induced response in experimental models in pulmonary cells [7,32]. These studies have shown that beneficial effects of sevoflurane on LPS-mediated damage involve a reduction of cell death, an attenuation of the inflammatory response and chemotactic mechanisms, as well as an increase in the expression of molecules that protect cells against injury such as the chaperone HSP-32.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of our results are also observed at 7% sevoflurane, indicating that its dosage might differentially affect cell types. For example, postconditioning with up to 6% sevoflurane has shown beneficial effects in hippocampal tissue [30]. …”
Section: Discussionmentioning
confidence: 99%
“…The neuronal cultures were then directly placed in an anaerobic incubator (Thermo, Waltham, MA, USA) containing 100 % N 2 at 37°C. After 90 min in OGD, the cultures were removed from the anaerobic incubator, immediately washed three times with BSS before adding an equal volume of Neuorbasal medium/B27/glutamine/gentamycin and incubated in a standard cell incubator containing 5 % CO 2 , 95 % air balance, 98 % humidity at 37°C for 24 h. In the sevoflurane post-conditioning protocols, neuronal cultures were exposed immediately in a Billups-Rothenburg chamber that was bubbled with different concentrations of sevoflurane in 95 % air-5 % CO 2 at 6 L/min for 7-8 min after OGD [21]. Then the chamber was kept tightly sealed for 1 h at 37°C and the concentrations of sevoflurane in exhaust gas from the chamber was confirmed by the Datex TM infrared analyzer (Capnomac, Helsinki, Finland).…”
Section: Ogd/r and Sevoflurane Post-conditioningmentioning
confidence: 99%